Migracje edukacyjne kobiet do Warszawy w perspektywie biograficznej = Educational migration of women to Warsaw biographical perspective - Lange, Pamela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the position of women from countryside and small towns who have emigrated to Warsaw because of educational reasons. The research was conducted on the basis of biographical in-depth interviews. The main objective of the study was to learn about the situation of women who were born and raised in smaller towns (villages and towns up to 100 thousand of residents), and then decided to migrate to Warsaw because of educational reasons. There was analyzed the ratio of the women to the capital, the motives which had guided them in making the decision to move away, the impact of origin on the identity of these women and their opinions about urban life.
Keywords: kobiety; migracje do miast; edukacja; perspektywa biograficzna; migracja horyzontalna; women; migration to the cities; education; horizontal migration; biographical perspective